Peripheral Perfusion Index in Assessment of Shock in Paediatric Intensive Care Unit of A Tertiary Care Hospital - Ullah, Monir; Biswas, Suman; Islam, Md Saiful; Hossain, Mohammed; Amin Chowdhury, Muhammad Jabed Bin; Chowdhury, Rana; Meah, Mohammad Musa; Mahmud, Nasir Uddin; Ahmed, Farid Uddin (IAHS Medical Journal, 2022)
Background: Measures of peripheral perfusion can be used to assess the hemodynamic status of critically ill patients. The peripheral Perfusion Index (PI) based on analysis of the pulse oximetry signal has been implemented in monitoring systems as an index of peripheral perfusion. The aim of this study was to evaluate clinical state of shock by PI in a Pediatric Intensive Care Unit (PICU) of a tertiary care hospital of Bangladesh. Materials and methods: This prospective observational study was carried out in the PICU of Chittagong Medical College Hospital. Children aged 1 month to 12 years who needed hemodynamic monitoring were included and categorized into five age groups. Demographic data, vital parameters and PI were recorded. Hemodynamic monitoring was started as early as possible within 24 hours of arrival in PICU, then 30 minutes after, then 8 hourly for a total 4 observations. Results: In total, 199 children were included with or without features of shock and 796 hemodynamic measurements were taken and analyzed. Mean/median PIs were significantly higher in patients without shock compared to patients with shock in all age groups except age group 10-12 years of age. Clinical shock can be reasonably detected when PI value was < 1.25 in children <1 year of age, < 2.05 in 1 to 3 years of age, <2.55 in 3 to 5 years, and <1.95 in 5-10 years of age. These values had low sensitivity but high specificity in detecting clinically assessed shock in that particular age group. Overall, PI had good correlation with systolic, diastolic, mean arterial blood pressure and pulse pressure. Children with different features of shock had significantly lower mean PI compared to children without features of shock. Conclusion: PI can be used as a non-invasive, continuous parameter to monitor peripheral perfusion in critically ill children managed in PICU. IAHS Medical Journal Vol 4(2), December 2021; 46-50